Estudo da estereoquímica dos alcaloides piperidínicos de Senna spectabilis (Fabaceae) e suas implicações na atividade anticolinesterásica - Freitas, Thamires Rodrigues (2022)
Senna spectabilis (Fabaceae) is an important source of chiral alkaloids, from which the major homologous alkaloids, (–)-cassine and (–)-spectaline, as well as two diastereomers, 6-isocassine and 6-isospectaline, were isolated. Mixtures of homologous pairs were resolved by high performance liquid chromatography, with the four isolated compounds having their relative configuration determined by NOESY 1D nuclear magnetic resonance experiments. Additionally, the majority alkaloids had their absolute configuration determined by the Mosher method. The 3-position asymmetric carbon (C-3) of both (–)-cassine and (–)-spectaline, were marked as (–)-R. Thus, together with the results of the NOESY 1D experiments, it was also possible to determine the absolute configuration of C-2 and C-6 for (–)-cassine and (–)-spectaline, as well as to suggest for diastereomers 6-isocassine and 6-isospectaline, being (–)-2R,3R,6S-cassine, (–)-2R,3R,6S-spectaline, 2R,3R,6R-isocassine and 2R,3R,6R-isospectaline. With the absolute configuration assured, it was possible to verify the anticholinesterase potential of the alkaloids as inhibitors of the enzymes acetylcholinesterase, with (–)-cassine (IC50 14.5 μM) and (–)-spectaline (IC50 29.9 μM) were more potent when compared to 6-isocassine (IC50 751.5 μM) and 6-isospectaline (IC50 2950.5 μM), respectively, indicating that the absolute configuration of the asymmetric carbon at position 6 (C-6) is fundamental for the activity.